(1-x)Bi0.5Na0.47Li0.03TiO3-xNaNbO3 lead-free ceramics with superior energy storage performances and good temperature stability. Issue 17 (1st September 2022) - Lu, Ying; Li, Peng; Du, Juan; Fu, Peng; Hao, Jigong; Zeng, Huarong; Li, Wei
Abstract: Dielectric capacitors show great potential in superior energy storage devices. However, the energy density of these capacitors is still inadequate to meet the requirement of energy storage applications. In this study, the Bi0.5 Na0.47 Li0.03 TiO3 - x NaNbO3 (BNLT- x NN) ceramics were prepared via conventional solid-phase reaction. Results showed that NN can efficaciously enhance the breakdown strength ( E b ) and the relaxation behavior of the BNLT ceramic because of the broken ferroelectric long-range order. When x  = 0.3, the maximum E b reached 350 kV/cm, at which the 0.7BNLT-0.3NN ceramic exhibited the high recoverable energy storage density ( W rec ) of 4.83 J/cm 3 and great efficiency ( η ) of 78.9%. The ceramic demonstrated good temperature stability at 20 °C-160 °C and excellent fatigue resistance. Additionally, the 0.7BNLT-0.3NN ceramic presented high power density ( P D ; ∼77.58 MW/cm 3 ), large current density ( C D ; ∼861.99 A/cm 2 ), and quite short discharge time ( t 0.9 ; ∼0.090 μs). These results indicated that the 0.7BNLT-0.3NN material has excellent energy storage properties and various application prospects.